Na teraz plz
Zad. 1.

Wykonaj działanie

a) (a-6)2

b) (2x-3y)2

c) (2a+5)2-(2a-5)(2a+5)

d) (√3 -1)(√3 +1)

e) (3√5 - √10)2

f) (6 +4x)(4x-6)

g) (2x+1)2 – (2x-1)(1+2x) – (2x -5)2

Zad. 2

Usuń niewymierność z mianownika √33+√3

Zad. 3* (dodatkowe)

Oblicz

(√2+√5 -√√5−2)2=
pomocy



Odpowiedź :

Odpowiedź:

a)(a-6)²=a²-12a+36

b)(2x-3y)²=4x²-12xz+9y²

c)(2a+5)²-(2a-5)(2a+5)=4a²+20a+25-(4a²-25)=4a²+20a+25-4a²+25=20a+50

d)(√3-1)(√3+1)=3-1=2

e)(3√5-√10)²=45-6√50+10=55-30√2

f)(6+4x)(4x-6)=16x²-36

g)(2x+1)²-(2x-1)(1+2x)-(2x-5)²=

4x²+4x+1-(4x²-1)-(4x²-20x+25)=

4x²+4x+1-4x²+1-4x²+20x-25=

-4x²+24x-23

zad 2

[tex]\frac{\sqrt{33}}{\sqrt{3}}=\frac{\sqrt{33}*\sqrt{3}}{\sqrt{3}*\sqrt{3}}=\frac{\sqrt{99}}{3}[/tex]= [tex]\frac{3\sqrt{11}}{3}=\sqrt{11}[/tex]

zad 3

(√2+√5-√5-2)²=

(√2-2)²=2-4√2+4=6-4√2

Szczegółowe wyjaśnienie: